An Investigation of How Social Media Opinion Leaders Impact on Chinese Millennials’ Purchase Decision and to Evaluate the Effectiveness of the Influence During the Decision-Making Process. - GENG, Mingze (2017)
With the increasing popularity on social media usage, and the growing up of digital natives, social media has become one of the most important market and tool for marketing promotion activities.